Severe acute malnutrition: seasonal variations in Southern Rajasthan, India - Singla, Sanjay; Suman, Rameshwar L.; Meena, Pradeep; Goyal, Suresh; Jain, Rupali; Meena, Suresh (International Journal of Research in Medical Sciences, 2016)
Background: Malnutrition is India’s one of the biggest health care challenge. India has some of the highest rates of child malnutrition. We performed a retrospective study of children admitted in Malnutrition Treatment Centre to find out any seasonal variations in the prevalence of severe acute malnutrition (SAM) in Southern Rajasthan, India. Methods: In this hospital based retrospective study, data were analysed for all children admitted at malnutrition treatment centre of a tertiary level hospital attached to a medical college from April 2014 to March 2016 to study the seasonal variations in the prevalence of SAM. Results: A total of 30,140 children were admitted during the last two years, out of which under five children other than new born were 4,942 in 2014-15 and 5,972 in year 2015-16. Total 1915 SAM children were admitted in our malnutrition treatment centre (MTC) in last 2 years. Among the under five children 840 (17%) children were admitted with SAM in 2014-2015 and 1075 (18%) in year 2015-2016. The number of SAM admission has increased in 2015-16 from the previous year (p<0.05). On an average 70±22.31 children were admitted per month in 2014-15 while average of 89.58±16.82 children were admitted in year 2015-16. There was no significant seasonal variation during both the years when analysed on the basis of months (p>0.05). Conclusions: The prevalence of SAM in admitted patients was high as compared to national and state data and this has increased over the year, but there are no month wise seasonal variations in prevalence of SAM in our children representing Southern Rajasthan, India.